The Dynamics of Reference and Shared Visual Attention - Dale, Rick; Kirkham, Natasha Z.; Richardson, Daniel C. (Frontiers in Psychology, 2011)
In the tangram task, two participants are presented with the same set of abstract shapes portrayed in different orders. One participant must instruct the other to arrange their shapes so that the orders match. To do this, they must find a way to refer to the abstract shapes. In the current experiment, the eye movements of pairs of participants were tracked while they were engaged in a computerized version of the task. Results revealed the canonical tangram effect: participants became faster at completing the task from round 1 to round 3. Also, their eye-movements synchronized over time. Cross-recurrence analysis was used to quantify this coordination, and showed that as participants’ words coalesced, their actions approximated a single coordinated system.